Comparison of clinical outcomes and patient satisfaction in immediate single-stage versus two-stage implant-based breast reconstruction - Susarla, Srinivas M; Ganske, Ingrid; Helliwell, Lydia; Morris, Donald; Eriksson, Elof; Chun, Yoon S (Plastic and reconstructive surgery (1963), 2015)
The purpose of this study was to assess the outcomes of immediate, single-stage, implant-based reconstruction compared with traditional, two-stage reconstruction (i.e., tissue expander placement followed by exchange to implant). A retrospective review of consecutive patients who underwent immediate unilateral or bilateral breast reconstruction over an 8-year period was performed. The primary predictor variable was method of reconstruction (single-stage versus two-stage). Outcome measures were postoperative complication rates, revision rates, and BREAST-Q patient satisfaction scores. Descriptive, bivariate, and multiple regression statistics were computed. The study sample consisted of 346 subjects who underwent reconstruction of 582 breasts (166 single-stage and 416 two-stage reconstructions). Complication rates between the single-stage and two-stage groups were similar for minor infections, major infections, hematoma formation, seroma formation, minor necrosis, and major necrosis (p ≥ 0.20). In a multiple logistic regression model, subjects undergoing single-stage reconstruction were found to be 87 percent more likely to require revision necessitating an additional operation (p = 0.005). In an adjusted regression model, subjects undergoing two-stage reconstruction had higher BREAST-Q scores for satisfaction with medical and office staff (p ≤ 0.02). Subjects undergoing single-stage reconstruction had higher sexual well-being satisfaction scores. There is no significant difference in complication rates between single-stage versus two-stage implant-based breast reconstructions. Although single-stage reconstruction is associated with higher sexual well-being satisfaction, it is more than 80 percent more likely to require additional operative revisions. Two-stage reconstruction is associated with significantly higher satisfaction with the medical and office staff. Therapeutic, III.